Macromol. Chem. Phys. 19/2015. Issue 19 (1st October 2015) - Einert, Marcus; Wessel, Claas; Badaczewski, Felix; Leichtweiß, Thomas; Eufinger, Christine; Janek, Jürgen; Yuan, Jiayin; Antonietti, Markus; Smarsly, Bernd M.
<x xml:space="preserve">Abstract</x> Front Cover: Electrospinning and carbonization of poly(ionic liquids) (PILs) into fiber mats is demonstrated to produce carbonaceous fiber mats with high electric conductivity. Systematic analysis provides insight into the structural development, and shows that electrical conductivity of the disordered nitrogen‐enriched carbon mats is influenced by the complex interplay of the atomic microstructure, the amount and the nature of nitrogen dopant, and the overall chemical composition. Further details can be found in the article by M. Einert, C. Wessel, F. Badaczewski, T. Leichtweiß, C. Eufinger, J. Janek, J. Yuan, M. Antonietti, and B. M. Smarsly* on page 1930.